Tandem Gait Test-Retest Reliability Among Healthy Child and Adolescent Athletes - Howell, David R. (J Athl Train, 2019)
CONTEXT: The tandem gait test is a method for assessing dynamic postural control and part of the Sport Concussion Assessment Tool, versions 3 and 5. However, its reliability among child and adolescent athletes has yet to be established. OBJECTIVE: To examine the test-retest reliability of the single-task and dual-task tandem gait test among healthy child and adolescent athletes. DESIGN: Descriptive laboratory study. SETTING: Sports injury-prevention center. PATIENTS OR OTHER PARTICIPANTS: Uninjured and healthy athletes between the ages of 9 and 18 years. INTERVENTION(S): Tandem gait measures repeated 3 times across the period of approximately 1 month. MAIN OUTCOME MEASURE(S): Participants completed the tandem gait test under single-task and dual-task (ie, while simultaneously executing a cognitive task) conditions. Our primary outcome measure was completion time during the single-task and dual-task conditions. We also assessed cognitive accuracy and response rate while participants completed the dual-task tandem gait test. RESULTS: Thirty-two child and adolescent athletes completed the study (mean age = 14.3 ± 2.4 years; females = 16). Single-task tandem gait times were similar across the 3 testing sessions (14.4 ± 4.8, 13.5 ± 4.2, and 13.8 ± 4.8 seconds; P = .45). Dual-task tandem gait times steadily improved across the test timeline (18.6 ± 6.9, 16.6 ± 4.5, and 15.8 ± 4.7 seconds; P = .02). Bivariate correlations indicated moderately high to high agreement from test 1 to test 2 (single-task r = .627; dual-task r = 0.655) and from test 2 to test 3 (single-task r = 0.852; dual-task r = 0.775). Both the single-task (intraclass correlation coefficient; ICC [3,1] = 0.86; 95% confidence interval [CI] = 0.73, 0.93) and dual-task (ICC [3,1] = 0.84; 95% CI = 0.69, 0.92) conditions demonstrated high reliability across testing sessions. CONCLUSIONS: Tandem gait outcome measures demonstrated high test-retest reliability in both the single- and dual-task conditions. The overall reliability was within the acceptable range for clinical practice, but improvements across tests suggested a moderate practice effect. Tandem gait represents a reliable, dynamic, postural-control test that requires minimal space, cost, and time.